Does ultrasonographic volume of the thyroid gland correlate with difficult intubation? An observational study - Meco,Basak Ceyda (2015)
BACKGROUND AND OBJECTIVES: Preoperative ultrasonographic evaluation of the thyroid gland done by surgeons could let us foresee airway management challenges. The aim of this observational study was to evaluate the effects of thyroid-related parameters assessed preoperatively by surgeons via ultrasonography and chest X-ray on intubation conditions. METHODS: Fifty patients undergoing thyroid surgery were enrolled. Thyromental distance, Mallampati score, neck circumference and range of neck movement were evaluated before the operation. Thyroid volume, signs of invasion or compression and tracheal deviation on chest X-ray were also noted. The intubation conditions were assessed with Cormack and Lehane score and the intubation difficulty scale. Statistical analyses were done with SPSS 15.0 software. RESULTS: The mean thyroid volume of the patients was 26.38 ± 14 mL. The median intubation difficulty scale was 1 (0-2). Thyromental distance (p = 0.011; r = 0.36; 95% CI 0.582-0.088), Mallampati score (p = 0.041; r = 0.29; 95% CI 0.013-0.526), compression or invasion signs (p = 0.041; r = 0.28; 95% CI 0.006-0.521) and tracheal deviation on chest X-ray (p = 0.041; r = 0.52; 95% CI 0.268-0.702) were correlated with intubation difficulty scale. Also patients were classified into two groups related to their intubation difficulty scale (Group I, n = 19: intubation difficulty scale = 0; Group II, n = 31: 1 < intubation difficulty scale ≤ 5) and difficult intubation predictors and thyroid-related parameters were compared. Only Mallampati score was significantly different between groups (p = 0.025). CONCLUSION: The thyroid volume is not associated with difficult intubation. However clinical assessment parameters may predict difficult intubation.